(untitled) (Advances in Applied Mathematics and Mechanics, 2025)
This paper investigates a novel nonlinear singular fractional SI model with the Φ_p operator and the Mittag-Leffler kernel. The initial investigation includes the existence, uniqueness, boundedness, and non-negativity of the solution. We then establish Hyers-Ulam stability for the proposed model in Banach space. Optimal control analysis is performed to minimize the spread of infection and maximize the population of susceptible individuals. Finally, the theoretical results are supported by numerical simulations.